Settlement of Illegal Building Disputes on the Edge of the Sukalila River, Cirebon City, with Justice - Ari Nurhaqi; Sanusi Sanusi (Ann Publisher, 2025)
Background. Illegal buildings along the Sukalila River in Cirebon city, mostly MSME-based businesses, pose complex legal, environmental, and social problems. Disputes between local governments that have the authority to arrange space with communities that have illegal buildings often arise from inconsistencies between the provisions for erecting buildings on the river and the community's need to make a living. Purpose. This research aims to analyze the form of illegal building dispute resolution that is not only in accordance with the law but also fair to affected communities. Method. The research method is used for empirical juridical or sociological research through regulatory studies, document analysis, and practical field studies on the management of watersheds or river equivalents. Results. This research shows that fair settlement needs to integrate the principles of procedural, distributive, and restorative justice. Mediation mechanisms, participatory dialogue, objective data collection, and the inclusion of new relocations are effective steps to reduce conflicts. In addition, it once again prohibits the existence of illegal buildings and is intended to promote beautiful urban development. Conclusion. This study concludes that a collaborative, empowerment-based dispute-resolution model is the key to achieving social justice and sustainable management of the Sukalila River.